Socially desirable responses and attitudes towards people with intellectual disabilities in education and rehabilitation students - Nikolić, Milena; Šeatović, Stevan (Specijalna edukacija i rehabilitacija, 2022)
Introduction. Research suggests a link between socially desirable responses (SDR) and attitudes towards people with disabilities. Objectives. The main aim was to examine the relationship between the expressed tendency of education and rehabilitation students to give socially desirable responses, the expressed discomfort and fear in interactions, and the frequency of contact with people with intellectual disabilities. The specific objectives of the research were: to examine whether there was a difference in the manifestation of socially desirable responses, discomfort and fear, and the frequency of contact with regard to the year of study and the study program; to examine the relationship between discomfort and fear and the frequency of contact while controlling socially desirable responses; to determine which variables affected the expression of discomfort and fear. Methods. The survey was conducted on a convenient sample of 100 students of education and rehabilitation. Seventy-one percent of students attended the first and second year, while 29.0% attended the third and fourth year. Fifty-eight percent of students attended Special Education and Rehabilitation, 27.0% attended Speech and Language Pathology and Audiology, and 15% attended Behavioral Disorders. The Scale for Social Desirability, the Interaction with Disabled Persons Scale, and the Contact with Disabled Persons Scale were applied. Results. The results showed a weak negative correlation between discomfort and fear and the propensity to SDR, frequency of contact, and the year of study. The correlations between discomfort and fear and the frequency of contact were statistically significant even when socially desirable responses were controlled. There were no differences with regard to the study program. The difference regarding the year of study existed in the manifestation of discomfort and fear, where first and second-year students achieved the highest score. The tendency to give socially desirable responses and the year of study had the greatest impact on the expressed level of discomfort and fear. Conclusion. Future research on attitudes towards people with disabilities should consider the tendency towards socially desirable responses and try to control it.
Keywords: attitudes; discomfort and fear; frequency of contact; socially desirable responses; students of education and rehabilitation